IPCS mode of action framework. - International Programme on Chemical Safety (Harmonization project document, 2007)
Part 1. IPCS framework for analysing the relevance of a cancer mode of action for humans and case-studies - part 2. IPCS framework for analysing the relevance of a non-cancer of action for humans.